2021
DOI: 10.1039/d1sc01310f
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium-modification enhances photocatalytic CO2 reduction on ZnSe quantum dots

Abstract: Colloidal photocatalysts are a promising, low-cost material to utilize solar light for the conversion of CO2 to carbon-based fuels, but controlling the product selectivity for CO2 reduction remains challenging, in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 62 publications
4
43
0
Order By: Relevance
“…The photocatalytic performance was investigated in an aqueous ascorbic acid (AA) solution (3 mL, 0.1 M) under a constant flow of CO 2 (4 sccm) using automated in-line gas chromatography by irradiating the samples with UV-filtered simulated solar light ( λ > 400 nm, AM 1.5 G, 100 mW cm −2 ; see ESI † for details). Unexpectedly, we find that the dithiols can activate the bare ZnSe–BF 4 for enhanced CO 2 RR at conditions similar to the previously optimized system 17 with a strong dependence on the dithiol length (black trace in Fig. 2 and Table S1 † ).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The photocatalytic performance was investigated in an aqueous ascorbic acid (AA) solution (3 mL, 0.1 M) under a constant flow of CO 2 (4 sccm) using automated in-line gas chromatography by irradiating the samples with UV-filtered simulated solar light ( λ > 400 nm, AM 1.5 G, 100 mW cm −2 ; see ESI † for details). Unexpectedly, we find that the dithiols can activate the bare ZnSe–BF 4 for enhanced CO 2 RR at conditions similar to the previously optimized system 17 with a strong dependence on the dithiol length (black trace in Fig. 2 and Table S1 † ).…”
Section: Resultssupporting
confidence: 78%
“…per QD, similarly to the previously reported ligand 3-(2-mercaptoethyl)-1-methyl-imidazolium (MEMI). 17 In the second regime, the signals associated with the ligands are detectable by NMR but are broadened. This broadening indicates that the ligands are in close vicinity of the QD surface which leads to an anisotropic chemical environment for the protons that causes the peaks to broaden – essentially caused by a superposition of many slightly shifted peaks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Since the seminal work published in Science in 2011 by Rosen et al, 47 numerous experiments have reported that the inclusion of imidazolium-based ILs in the electrolyte promotes the electrochemical reduction of CO 2 , regardless of catalyst choice. [48][49][50] However, there has been no unified picture of the role of the IL. 51 In the reaction pathway of CO 2 electroreduction to CO, three elementary steps are usually considered: (1) CO 2 molecules adsorbed on the catalyst surface gain an electron from the electrode catalyst and a proton from the electrolyte (i.e., proton-coupled electron transfer; PCET) to form *COOH, (2) another proton-electron pair is transferred to *COOH, forming *CO and H 2 O, and (3) CO desorbs from the catalyst surface.…”
Section: First-principles Based Parametrization For Accurate Descript...mentioning
confidence: 99%
“…ZnSe-BF 4 QDs in the absence of a co-catalyst are highly active toward the H 2 evolution reaction by reducing aqueous protons (Figure S6) and only form traces of CO from CO 2 as reported previously. 25,26 Significant amounts of CO are only produced in the presence of co-catalysts, and the best-performing co-catalyst (Co(qpy), Ni(cycP), and Co(tppS3N1)) of the three catalyst families (quaterpyridine, cyclam, porphyrin) were analyzed in detail (see Figure 3 and Table S2). All QD-co-catalyst hybrids were optimized with respect to co-catalyst loading (optimum 20 mol co-catalyst mol QD −1…”
Section: ■ Introductionmentioning
confidence: 99%